Meteorology today an introduction to weather, climate, and the environment - Ahrens, C. Donald; Henson, Robert (Australia Cengage Learning, 2016)
Meteorologist C. Donald Ahrens and new co-author Robert Henson combine the latest in weather, climate, and earth science to introduce students to Meteorology Today, 11th Edition. Grounded in the scientific method, this engaging and highly visual text shows students how to observe, calculate, and synthesize information as budding scientists, systematically analyzing meteorological concepts and issues. Specific discussions center on severe weather systems, such as tornadoes, thunderstorms, and hurricanes, as well as everyday elements, such as wind, precipitation, condensation, masses and fronts, and the seasons...--Provided by the publisher.
Earth and its atmosphere -- Energy: warming the earth and the atmosphere -- Seasonal and daily temperatures -- Atmospheric humidity -- Condensation: dew, fog, and clouds -- Stability and cloud development -- Precipitation -- Air pressure and winds -- Wind: small-scale and local systems -- Wind: global systems -- Air masses and fronts -- Middle-latitude cyclones -- Weather forecasting -- Thunderstorms -- Tornaedos -- Hurricanes -- Earth's changing climate -- Global climate -- Air pollution -- Light, color, and atmospheric optics.
Includes index.
Keywords: Meteorology -- Textbooks